Analysis of Factors Affecting MSME in Using Fintech Lending as Alternative Financing: Technology Acceptance Model Approach - Arif Rahadian; Hakiman Thamrin (BBR: Brazilian Business Review)
This study aims to determine factors impacting the intention of Micro, Small, and Medium Enterprises (MSMEs) in using fintech lending applications as an optional source of business financing using the technology acceptance model approach. The population in this study were MSMEs in Indonesia. Samples were taken by purposive sampling with the criteria of having used a licensed fintech lending application for business financing. The samples used were 171 samples. This study used structural equation model (SEM) as the analysis technique. The results of this study showed that Perceived Ease of Use had an impact on Perceived Usefulness but had no effect on Attitude Toward Using. The factor Perceived Usefulness had an effect on Attitude Toward Using, and Attitude Toward Using influences Behavioral Intention to Use. Fintech companies can play a role by providing education and empowerment to foster understanding of digital literacy for MSME stakeholders. The governments need to develop policy frameworks that can balance innovation and risk mitigation.